Nitrogen dopedTiO2 photoactive in visible light - Pérez, Eliana Guadalupe (2015)
In this research TiO2 modified with nitrogen has been prepared. The synthesis method used was sol gel from the hydrolysis of titanium tetrabutoxide with urea solution, combined with a low temperature treatment at atmospheric pressure. The theoretical mole ratio N/Ti was equal to 0.5 and the theoretical mole ratio HNO3/TiO2 was equal to 0.5. The solid obtained was calcined at different temperatures in static air with high heating rate and residence time of 1 hour. The samples were characterized by X-ray diffraction, FTIR Raman and diffuse reflectance spectroscopy, thermodifferential and thermogravimetric analysis and specific surface area. All calcined solids exhibit absorption in the visible range. The Raman spectroscopy and X-ray diffraction revealed for all the heat treatments, the presence of crystalline phases corresponding to anatase and brookite polymorphism. The photocatalytic activity of the catalysts was tested in degradation of an artificial dye under visible light, yielding the best results for the sample treated at 250°C. Our results allow to say that this behaviour is due to the absorption of visible light, good efficiency for the adsorption of the dye and presence of two crystalline phases that decreases the recombination of photogenerated electrons and holes. The synthesis technique used allows obtaining solids with textural and attractive photocatalytic properties.